Changes in physical and biochemical aspects during fruit ripening of banana cultivars (Musa spp.) (Research, Society and Development, 2020)
The aim of the present study was to evaluate the color, texture (firmness), content of total phenolic compounds (TPC) and enzyme activity of pectinamethylesterases (PME) and polygalacturonases (PG) in different banana cultivars (‘Silver’, ‘Apple’ and ‘Dwarf cavendish’) during different ripening stages. All results were subjected to the Scott-Knott test (p < 0,05) and to the Principal Component Analysis (PCA). It was verified statistical differences between the stages in each cultivar and between the cultivars in each stage. In comparison between the cultivars, the ‘Silver’ banana had a higher shade of green in stage 1 and the ‘Dwarf cavendish’ banana presented in stage 3 the most accentuated yellow color. During the ripening of the three banana cultivars, it was possible to verify that there was a decrease in firmness and TPC, as well as an increase in the enzymatic action of PME and PG, characterizing the banana softening during ripening, confirmed by the PCA. It is concluded that the cultivar and the stage of ripeness of banana directly interfere in the evaluated parameters.